Analysis of Youth Interest In Agriculture - Muh Ardiyansa Baharuddin; Fitriani R; Aksal Mursalat (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2025)
Indonesia is known as an agricultural country with abundant natural resources, but this condition does not necessarily mean that Indonesians have easy and affordable access to food. Indonesia has been known as a food importer in recent decades. However, serious problems remain in the agricultural workforce. The main problem is the shift in demographic structure that is unfavourable for the agricultural sector, namely the increasing number of older farmers (over 55 years old), while the younger workforce is decreasing. This phenomenon of ageing farmers (ageing farmers) and the decreasing interest of young workers in the agricultural sector. The purpose of this study is to examine how urbanisation, education level, income factors influence youth interest in agriculture. This research was conducted in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency from November to December 2024. The population was 42 young farmers in Bulo Village aged 16-30 years. The data analysis technique used was Multiple Linear Regression Analysis. The results of this study indicate that from the F Test (Simultaneous), all Independent Variables (X) have a significant effect on the Dependent Variable (Y). Meanwhile, the T Test (Partial) Urbanisation Variable (X1), Education Level Variable (X2), and Income Variable (X3) have a significant effect on the Interest (Y) of the young generation in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency.